Towards sonic injection in Peirce-Smith converters: A computational fluid dynamics (CFD) Modelling Study - Chibwe, D.; Akdogan, G.; Bradshaw, S.; Bezuidenhoudt, G.; Davis, J.; Eksteen, Jacques; Kapusta, J. (MetSoc Publication, 2012)
This research work forms part of an assessment to complement the feasibility of implementing high pressure sonic injection into relatively small (2.25 m I.D by 3.66 m I.L) Peirce-Smith converters (PSC) used at Lonmin Plc. Work has been carried out to characterize the fluid dynamics of three-phase (air, matte and slag) fluid flow in these converters using Computational Fluid Dynamics (CFD) simulations. The investigation has been done to study the flow pattern of the three phase system at high air pressure injection achieving sonic velocity at the tuyere exit into the converter. The 2-D and 3-D simulations of the three phase system were carried out using the volume of fluid (VOF) and realizable k - ε turbulence models to account for the multiphase and turbulence nature of the flow, respectively. These models were implemented using the commercial CFD numberical code FLUENT. A detailed study of the flow pattern has been presented in the form of contour plots and the results obtained are useful for understanding plume extension and velocity distribution, shear wall stress distribution, and phase distribution characteristics in the system. The results provide a basis for further development of sonic injection technology into relatively small industrial Peirce-Smith converters with the ultimate objective of achieving lower energy comsumption, improved process efficiency and increased throughput of the converting process.